Changes in maxillary dental arch morphology after implant treatment in the alveolar cleft region. Issue 4 (20th December 2020) - Ahn, Kilwoo; Sato, Hitoshi; Kurihara, Yuji; Ogura, Hiroshi; Shirota, Tatsuo
Abstract: Background: Few reports have examined dental arch morphology (DAM) after dental implant placement in cleft patients and its actual state is unclear. Objective: To analyze the presence of changes in DAM and influencing factors in cleft lip and/or palate (CLP) patients who receive implant treatment in the alveolar cleft region. Methods: Subjects comprised 20 CLP patients in whom maxillary dental arch width (DAW) was evaluated before and after implant treatment based on computed tomography data. First, widths between the canines (W3), between the first premolars (W4), between the second premolars (W5), and between the first molars (W6) were measured before and after surgery. Changes in distance were analyzed using the Wilcoxon signed‐rank test, revealing a significant increase in W6. Analysis of Co‐Variance was performed with the difference in W6 after implant treatment as the response variable, and the following six items as explanatory variables: sex; cleft type; age at alveolar bone graft; time to implantation after bone grafting; number of implants; and time after completion of the observation period. Results: The reduction in W6 was larger in the order of complete bilateral CLP, complete unilateral CLP, and unilateral cleft lip and alveolus, and the change decreased with an increasing number of implants. Conclusions: Implant treatment of the alveolar cleft region may result in a slight reduction in width of the dental arch after treatment completion.